Major dietary patterns and their associations with diet quality indices in Iranian adults - Haghighatdoost, Fahimeh; Rashidi Pour Fard, Nafiseh; Karimi, Majid; Baghaei, Mohammad Hassan; Azadbakht, Leila (Progress in Nutrition, 2018)
Background: Limited data on the association of dietary patterns with nutrient intakes and diet quality indices are available. Objective: We examined the relation of dietary patterns and diet quality indices and nutrient intakes among Iranian. Methods: This cross-sectional study was conducted among 389 Isfahani adults. Dietary intakes were estimated using a validated semi-quantitative food frequency questionnaire. Dietary patterns were identified using factor analysis method. Diet quality indices [nutrient adequacy ratio (NAR), Mediterranean (MED) score, healthy eating index (HEI), dietary diversity score (DDS) and dietary energy density (DED)] were calculated according to standard methods. Results:  We identified four dietary patterns: healthy, high animal fat and protein, traditional and Western patterns. Participants in the top tertile of healthy dietary pattern, in comparison with those in the first tertile, had greater NARs for all nutrients of concern, HEI (73.5±6.8 vs.67.7±6.3; P